DEVELOPMENT OF SPECIAL PHYSICAL QUALITIES OF FOOTBALL PLAYERS (Rehabilitation and Recreation, 2024)
The main goal is to investigate the impact of the author’s methodology on the development of special physical qualities of football players of various roles. In these materials was described the use of the base of the sports complex of the NUWEE in Rivne, which was used by 20 football players of the experimental group who passed the stage of preliminary basic training, was determined. There are also 18 athletes of the national football team of the NUWEE (control group), who have repeatedly participated in competitions among the city’s universities. The following research methods were used: analysis of literary sources, practical experience, physical tests, statistical method, Mann-Whitney U-test. The obtained results indicate that for the development of the optimal level of physical and special qualities of football players of various roles, it is necessary to use rational means and training methods. In the context of the research, the author’s methodology contributed to the search for optimal ways of improving the profile physical and special qualities of the future sports specialization. Attention was paid to the individualization of the process of training football players relative to the physical and special qualities inherent in the athlete’s personality, which formed the basis of the author’s methodology. The high variability was an approach for the development of technical and tactical skills and special physical qualities, such as speed of reaction and decision-making, speed of movement on the field, explosive power, and coordination of movements. So, at the beginning of experimental studies, EG had a small difference in favor of CG in control tests. And at the end of the study, thanks to the use of the selected means and methods of training, significant changes are observed in the control types of tests, namely: “dribbling the ball 30 m” – “strikers” EG for 0.3 s (6.0±0.91); in “dribbling the ball 30 m with a circle of the uprights” – the “midfielders” of EG (7.3±0.1) improved the result by 0.8 s from the beginning of the study; “pull-up” in “attackers” and “defenders” of EG increased (15±1.30), which corresponds to the parameter of statistical significance p≤0.01. Conclusions. The improvement of the result is observed in all examined athletes, but any changes in the level of probability of values in these control tests weren’t detected. This can be explained by the fact that the dynamics of game techniques of players of different roles indicate, on the one hand, the previous level of development of special physical qualities, and on the other hand, a low probability of difference (Р > 0.05). The statement about the ambiguity of the level of probability of the values of changes indicates that improvements in results are observed, but not in all cases statistical significance is achieved. In general, our research has expanded the understanding of the influence of special physical qualities on the playing skills of football players of various roles and emphasized the importance of using individualized approaches in training.
Keywords: football players, role, physical and special qualities, technique